The Effect of the Combination of Resistance Band and Plyometric Training on the Shoot- ing Accuracy of Women's Futsal Players - Ilyas Kaisar Purnama; Anggi Setia Lengkana; Muhammad Nur Alif (Universitas Negeri Semarang, 2026)
The low shooting accuracy of female futsal players shows that the training program implemented has not been able to fully integrate aspects of physical condition and technical skills optimally, thus having an impact on the effectiveness of the final finish in game situations. This problem requires a more specific, structured, and contextual approach to training in accordance with the requirements of movement in futsal. This study aims to analyze the effect of the combination of resistance band and plyometric training on improving the shooting accuracy of female futsal players. The research method used a quantitative approach with a pre-experimental design in the form of a pretest-posttest design of one group to assess changes in abil- ity before and after treatment. The subjects were all female futsal players of Student Activity Unit of the University of Education Indonesia Sumedang which were de- termined through total sampling techniques. The research instrument used a target- based futsal shot accuracy test to objectively measure the level of shot accuracy. Data analysis was carried out through descriptive statistics to describe the initial and final conditions, as well as inferential statistics including normality tests, paired t-tests, and regression analyses to test the significance of differences and treatment contributions. The results of the study showed an increase in shooting accuracy after being given a training program, as indicated by an increase in the pretest average of 17.47 to 21.35 in the posttest, as well as a significance value of 0.001 < 0.05 so that the research hypothesis was accepted. These findings indicate that the combination of resistance bands and plyometric exercises is effective in improving shooting accuracy by improving movement control, stability, strength, and body coordination. Therefore, it can be concluded that this joint training program has a positive impact and contributes to the development of sports training science through a more integrated and applicable training approach.